Reimagining Innovation Amid the COVID-19 Pandemic: Insights From the WISH Innovation Programme - El Akoum, Maha; El Achi, Mahmoud (Frontiers in Public Health, 2021)
The World Innovation Summit for Health (WISH) hosts two innovation competitions as part of its biennial healthcare conference. During the COVID-19 pandemic, WISH received over 350 applications for both competitions, out of which 31 were shortlisted to showcase at the WISH 2020 virtual summit. Of the 31 showcasing innovations, 29% had suggested an alternative use to their innovation as a contribution to the global fight against COVID-19. As such, this article explores the apparent and urgent need for the repurposing of healthcare innovations as a way to reduce the costs and time associated with the conventional approach, in order to best respond to the demands of the global pandemic.